2005
DOI: 10.1044/1092-4388(2005/035)
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Stuttering Modification Therapy

Abstract: Nineteen adults who stutter participated in a 3-week intensive stuttering modification treatment program (the Successful Stuttering Management Program [SSMP]). A series of 14 fluency and affective-based measures were assessed before treatment, immediately after treatment, and 6 months after treatment. Measures included stuttering frequency; the Stuttering Severity Instrument for Children and Adults, Third Edition (SSI-3); a self-rating of stuttering severity; the Perceptions of Stuttering Inventory (PSI); the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(14 citation statements)
references
References 49 publications
1
8
0
3
Order By: Relevance
“…There is also much disagreement regarding the essential components of stuttering treatment for adults 3842. While many different treatment approaches exist to treat stuttering in adults, most of the approaches can be separated into two groups.…”
Section: Treatments For Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also much disagreement regarding the essential components of stuttering treatment for adults 3842. While many different treatment approaches exist to treat stuttering in adults, most of the approaches can be separated into two groups.…”
Section: Treatments For Adultsmentioning
confidence: 99%
“…Blomgren et al38 recently evaluated the clinical effectiveness of a three week intensive stuttering management program. The study indicated that the approach did not treat stuttered speech per se, but rather the acceptance, avoidance, stigmatic, and anxiolytic symptoms of the disorder.…”
Section: Treatments For Adultsmentioning
confidence: 99%
“…Dath[9] used hyno relaxation, breathing, relaxation, speech-prolongation technique and found these effective reduction of stuttering. More integrated interventions emerged that served in ameliorating stuttering, such as stuttering therapy,[10] Camperdown program. [11] In a review, Bothe (2006)[12] concluded that the powerful treatments for adults, with respect to both speech outcomes and social, emotional or cognitive outcomes, appear to combine variants of prolonged speech, self-management, response contingencies and other infrastructural variables.…”
Section: Introductionmentioning
confidence: 99%
“…Fun and enjoyment covers the need for pleasure, joy, laughing, playing, and having leisure time [14]. This result is supported by some studies [19][20][21]. It is often necessary to pay considerable attention to advanced stutterers' negative feeling and attitudes in therapy [22,23].…”
Section: Discussionmentioning
confidence: 79%